Fulminant Form of Hepatitis В in Children - A. L. Rossina (Detskie Infekcii (Moskva), 2016)
The article deals with the problem of fulminant viral hepatitis at the present stage. Are given their own observation of children, patients with fulminant hepatitis B. The data, including clinical examples show that fulminant hepatitis B occurs in born to HBV-infected mothers to infants during the first six months of life, which has not been evaluated vaccine prevention of hepatitis B, and is characterized by a high level of mortality.